Fluid shear stress-induced down-regulation of microRNA-140-5p promotes osteoblast proliferation by targeting VEGFA via the ERK5 pathway. (4th March 2022) - Wang, Xingwen; Geng, Bin; Wang, Hong; Wang, shenghong; Zhao, Dacheng; He, Jinwen; Lu, Fan; An, Jiangdong; Wang, Cuifang; Xia, Yayi
ABSTRACT: Purpose: Fluid shear stress (FSS) plays a critical role in osteoblast proliferation. However, the role of miRNA in osteoblast proliferation induced by FSS and the possible molecular mechanisms remain to be defined. The aim of the present study was to investigate whether miR-140-5p regulates osteoblast proliferation under FSS and its molecular mechanism. Materials and methods: miR-140-5p expression was measured by qRT-PCR. Western blot was used to measure the expressions of P-ERK1/2, ERK1/2, P-ERK5 and ERK5. The levels of VEGFA, PCNA, CDK4 and Cyclin D1 were identified through qRT-PCR and western blot, respectively. Cell proliferation was detected by CCK-8 assay and EdU labeling assay. Dual-luciferase reporter assay was used to validate the target of miR-140-5p. Results: miR-140-5p was significantly down-regulated when MC3T3-E1 cells were exposed to FSS. We then confirmed that up-regulation of miR-140-5p inhibited and down-regulation of miR-140-5p promoted osteoblast proliferation. In addition, FSS promotes osteoblast proliferation via down-regulating miR-140-5p. Luciferase reporter assay demonstrated that VEGFA is a direct target of miR-140-5p. Furthermore, transfection of mimic-140-5p inhibited the up-regulation of VEGFA protein level induced by FSS, suggesting that FSS regulates VEGFA protein expression via miR-140-5p. Further investigations demonstrated that VEGFA could promote osteoblast proliferation. Lastly, we demonstrated that miR-140-5p regulates osteoblast proliferation and ERK5 activation through VEGFA. Conclusions: Our study demonstrates that FSS-induced the down-regulation of miR-140-5p promotes osteoblast proliferation through activing VEGFA/ERK5 signaling pathway. These findings may provide a novel mechanism of FSS-induced osteoblast proliferation and offer a new avenue to further investigate osteogenesis induced by mechanical loading.